1982
DOI: 10.1002/jat.2550020405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of somatic and germ cell models for cytogenetic screening

Abstract: A variety of in vivo mammalian test models are available for screening of chemicals for mutagenicity at the chromosomal level. These models have been grouped into those focusing on somatic cell effects and those dealing with germ cell effects. An analysis of available literature indicates that 76 compounds have been tested from chromosome effects in both somatic and germ cells. Of these, concordant results (positive-positive or negative-negative) were obtained with 58 compounds. Of the remaining 18 compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Data presented by a number of groups [Holden, 1982;Adler and Ashby, 1989;Waters et al, 1993;Waters et al, 1994;Ashby and Tinwell, 2001;Tinwell et al, 2001] were used to argue that germ cell mutagens are detected by somatic cell mutation assays. This leads some to assume that any action to reduce exposure to somatic cell mutagens provides, by default, sufficient protection from any possible effects of germ cell mutagens, and it is likely the greatest contributor to the lack of significant regulatory attention in this subject.…”
Section: Assertion That Somatic Cell Mutagenicity Tests Are Also Su⁄cmentioning
confidence: 99%
“…Data presented by a number of groups [Holden, 1982;Adler and Ashby, 1989;Waters et al, 1993;Waters et al, 1994;Ashby and Tinwell, 2001;Tinwell et al, 2001] were used to argue that germ cell mutagens are detected by somatic cell mutation assays. This leads some to assume that any action to reduce exposure to somatic cell mutagens provides, by default, sufficient protection from any possible effects of germ cell mutagens, and it is likely the greatest contributor to the lack of significant regulatory attention in this subject.…”
Section: Assertion That Somatic Cell Mutagenicity Tests Are Also Su⁄cmentioning
confidence: 99%
“…An additional advantage of in vivo tests is that possible false positives arising from treatment conditions are eliminated [4]. Another attractive feature of a bone marrow micronucleus test is that Holden [5] in a review of 76 agents that have been tested in both bone marrow and germ cells, found that all the 26 germ cell mutagens were also active as clastogens in mouse bone marrow. Thus, these substances should already have been detected as positive in Ashby's short term in vivo strategy for the detection of carcinogens.…”
Section: Discussion On Mutagenicity Testing and Genetic Risk Assessmentmentioning
confidence: 99%
“…Different extrapolation models have been proposed for using animal test systems to predict human heritable mutations (eg. Davidson et al, 1986;Ehling, 1984;EPA, 1984;NRC, 1983;Sankaranarayanan, 1983;Holden, 1982;NRC, 1989;Sobels, 1989). Since strictly relevant human data demonstrating induced inherited effects are scanty and the human data that are available are equivocal (Narod et al, 1987;US Congress, OTS, 1986;NRC, 1983;Sankaranarayanan, 1983), the application of these models for human risk assessment is restricted at present.…”
Section: E Extrapolation From Animal Test Data To Humansmentioning
confidence: 99%
“…These extrapolations cannot be used to appraise the impact of diseases of different genetic aetiologies or the relative impact of somatic and germ cell effects on human ill-health. It is within this framework that epidemiology studies in human beings are needed (Sankaranarayanan, 1983;IPCS Environmental Health Criteria 46, 1985;Russell and Shelby, 1985;Holden, 1982;Russell, 1977;NRC, 1983).…”
mentioning
confidence: 99%